Axiological Analysis of the Driving Teacher's Perspective in Educational Philosophy on the Profile of Pancasila at SMAN 2 Kota Bima - Sarnita, Fitria; Suastra, I Wayan; Tungga Atmaja, Ananta Wikrama (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Learning at SMAN 2 Bima applies the concept of an independent curriculum with the strengthening of the Pancasila profile. Teachers are more skillful in using innovative learning models and media and strengthening student character.  This qualitative research collected related data from various sources of literature, interviews and observations, journals, news, and the internet. One of the elements in the independent learning curriculum is the Pancasila student profile. In order for its implementation to be implemented correctly, this must be studied. Talking about useful philosophical research means entering into the field of axiology. The ethical component, which belongs to the domain of axiology, is the focus of this research.